Hybrid pancreaticoduodenectomy as a transitional strategy: outcomes from a high-volume center - Long, Tran Cong Duy; Dat, Le Tien; Thanh, Nguyen Quoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Minimally invasive pancreaticoduodenectomy (MIPD) has been increasingly adopted; however, its implementation remains challenging, particularly during the early phase of program development. Hybrid pancreaticoduodenectomy, combining laparoscopic resection with extracorporeal reconstruction, has been proposed as a transitional approach. This study aimed to evaluate the perioperative outcomes of hybrid pancreaticoduodenectomy in a real-world setting. Methods: This retrospective study included consecutive patients undergoing hybrid pancreaticoduodenectomy at a high-volume tertiary referral center. To minimize selection bias, all patients who met predefined inclusion criteria during the study period were analyzed. Perioperative outcomes were assessed using standardized definitions, including postoperative pancreatic fistula (ISGPS 2016) and complications graded by the Clavien–Dindo classification. Results: A total of 138 patients were included, representing a consecutive and unselected cohort. Preoperative conditions were generally within acceptable ranges, although a subset of patients presented with obstructive jaundice and acute cholangitis, with selected cases undergoing preoperative biliary drainage. Most patients had a low postoperative pancreatic fistula risk profile. Perioperative outcomes were favorable. The median operative time was 277 minutes, and median blood loss was 200 mL. Major complications occurred in 6.5% of patients. Clinically relevant postoperative pancreatic fistula was observed in 8.7%, while most cases were biochemical leaks. The 90-day mortality rate was 1.4%. Conclusions: Hybrid pancreaticoduodenectomy is a safe and feasible approach with acceptable perioperative outcomes in a consecutive, unselected patient cohort. It represents a practical transitional strategy for the implementation of minimally invasive pancreatic surgery in routine clinical practice.